Nanocellulose: a promising material for engineering - an overview. (2017) - Ya'acob, Wan Mohd Hanif Wan; Aziz, Fauziah Abdul
Nanocellulose from abundant sources is attracting attention because it offers excellent properties. There are a number of sources that can be used to extract cellulose such as algae, bacteria, non-wood and wood materials. Numerous methods were established in order to isolate nanocellulose and each method produced different types of nanocellulose. However, there are some limitations in merging nanocellulose into polymeric material due to the presence of the hydrophilic group in nanocellulose structure. In order to overcome the limitations, surface modification method was introduced and may improve the homogeneity and interfacial interaction between nanocellulose and polymeric material. Utilising nanocellulose as reinforcement filler has successfully proved the hypothesis, where properties of the composite were enhanced according to several studies.